On Linguistic Emotivity with Bronisław Malinowski in the Background - Barański, Janusz (Poznańskie Studia Slawistyczne, 2015)
One of the ways of understanding linguistic emotivity is taking into account an anthropological approach. The first anthropologist who recognized the emotive aspect of language was the founding father of social anthropology Bronisław Malinowski, thus forming the foundation for future ethnolinguistics and linguistic anthropology. According to the view of these subdisciplines the role of speech cannot be defined only in terms of phonology, morphology or syntax but also in terms of semantics and pragmatics. Taking into account all the above mentioned aspects of language allows finding out basic oppositional functions of language: referential andemotive. The latter one means the impact of cultural contexts on language (eg. religious cult vs academic lecture), as well as the creative role of language that shapes the nature of communication and culture itself. Anthropological studies are followed in this respect by discussed below some approaches of linguistics, literary studies, philosophy and sociology.